(untitled) (Biological Sciences - PJSIR, 2001)
A significant (p<0.05) reduction in seed germination due to copper toxicity at 800 ppm was observed in A. lebbeck and L. leucocephala. A significant (p<0.05) effect on root length inA. lebbeck was observed at 500 ppm of copper treatment as compared to similar concentration of zinc treatment. Higher concentration of zinc element also decreased the seedling dry weight at 1100 ppm treatment inA. lebbeck and L. leucocephala. Shoot length ofL. leucocephala was more affected by copper treatment at 1100 ppm as compared to same concentration of zinc. The lower dose of copper at 200 ppm was found effective in decreasing the seedling growth ofL. leucocephala andA. lebbeck. Seedling growth rather than seed germination appears to be the sensitive stage for both tree species when treated with copper and zinc as compared to control. L. leucocephala was highly affected to copper and zinc toxicity, while A. lebbeck was less affected. According to tolerance test It was found that tolerance against zinc was higher as compared to copper.